"RichBlend" protocol for full-face filling and collagen biostimulation - Elizandra Paccola Moretto de ALMEIDA; Flávia Mauad LEVY; Marília Afonso Rabelo BUZALAF (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT The "RichBlend" protocol was designed for facial filling and collagen biostimulation, by means of a mixture of calcium hydroxyapatite (CaHA), hyaluronic acid (AH) and autologous platelet concentrates. This work reports the case of a 53-year-old patient with cutaneous photoaging, loss of facial volume, multiple rhythms in the frontal and periorbital regions, also marked skin flaccidity, especially the eyelid. The treatment was done with botulinum toxin (65 U) and the "RichBlend" protocol. Venipuncture was performed and the blood was centrifuged to obtain i-PRF (injectable platelet-rich fibrin) and plasma gel. After venipuncture and blood centrifugation, i-PRF and plasma gel were obtained. CaHA (Radiesse®) was diluted: a) in saline solution + i-PRF (hyperdilution) for biostimulationof the lower third of the face; and b) in AH (Juvederm Ultraplus XC®) + plasma gel, for hydrolifting on the forehead and dark circles, malar and temples. Plasma gel was applied to the nasogenian grooves and then the entire face was properly massaged. The "RichBlend" protocol rejuvenated the patient, as it promoted filling, volumizing, collagen formation (biostimulation), reduction of flaccidity, in addition to skin whitening. Since HA and CaHA are high-cost products, their mixture with autologous platelet concentrates, in liquid or gel form, allows the use of a greater amount of filled and biostimulator material on the face, at a more affordable cost.